To square the binomial (x-3), we will use the formula (a-b)^2 = a^2 - 2ab + b^2.
So, we have:
(x-3)^2 = x^2 - 2(x)(3) + 3^2
= x^2 - 6x + 9
Now we need to subtract 12 from the squared binomial:
(x^2 - 6x + 9) - 12
= x^2 - 6x + 9 - 12
= x^2 - 6x - 3
Therefore, the simplified expression for (x-3)^2 - 12 is x^2 - 6x - 3.
For this problem you will need to upload an image of your work. It can either be a screen shot of your work in desmos, or a picture of your hand written work.
Square the binomial and then simplify your answer.
(x−3)2−12
Click here to access this problem in Desmos
(1 point)
1 answer